A systematic review and meta-analysis of the effect of cognitive interventions to prevent intrusive memories using the trauma film paradigm. (March 2023) - Asselbergs, Joost; van Bentum, Jaёl; Riper, Heleen; Cuijpers, Pim; Holmes, Emily; Sijbrandij, Marit
Abstract: There is an unmet need for effective early interventions that can relieve initial trauma symptoms and reduce symptoms of posttraumatic stress disorder (PTSD). We evaluated the efficacy of cognitive interventions compared to control in reducing intrusion frequency and PTSD symptoms in healthy individuals using the trauma film paradigm, in which participants view a film with aversive content as an experimental analogue of trauma exposure. A systematic literature search identified 41 experiments of different cognitive interventions targeting intrusions. In the meta-analysis, the pooled effect size of 52 comparisons comparing cognitive interventions to no-intervention controls on intrusions was moderate ( g  = −0.46, 95% CI [–0.61 to −0.32], p < .001). The pooled effect size of 16 comparisons on PTSD symptoms was also moderate ( g  = −0.31, 95% CI [–0.46 to −0.17], p < .001). Both visuospatial interference and imagery rescripting tasks were associated with significantly fewer intrusions than controls, whereas verbal interference and meta-cognitive processing tasks showed nonsignificant effect sizes. Interventions administered after viewing the trauma film showed significantly fewer intrusions than controls, whereas interventions administered during film viewing did not. No experiments had low risk of bias (ROB), 37 experiments had some concerns of ROB, while the remaining four experiments had high ROB. To the best of our knowledge, this is the first meta-analysis investigating the efficacy of cognitive interventions targeting intrusions in non-clinical samples. Results seem to be in favour of visuospatial interference tasks rather than verbal tasks. More research is needed to develop an evidence base on the efficacy of various cognitive interventions and test their clinical translation to reduce intrusive memories of real trauma. Highlights: Unmet need for early interventions relieving initial trauma symptoms and PTSD symptoms. Moderate effect favoring cognitive interventions over control in reducing intrusions; low-moderate effect for PTSD symptoms. Data hint in favour of visuospatial tasks rather than verbal tasks.